The Effect of Media Advertising on the Behavior of Implementing Health Protocols in Pregnant Women during the Pandemic Period: Pengaruh Iklan Media terhadap Perilaku Penerapan Protokol Kesehatan Pada Ibu Hamil di Masa Pandemi - Febrina Dwi Nurcahyanti; Aprelsyan J. Loloda (Napande: Jurnal Bidan, 2022)
Background: Pregnant women are a group that is vulnerable to contracting the coronavirus, therefore it is better to take precautions according to health protocols. Knowledge of COVID-19 has a major effect on maintaining the health of the mother and fetus during pregnancy. Objectives: To determine the effect of media advertising on the behavior of implementing health protocols in pregnant women during the pandemic. Methods: pre-experimental type one group pre-post test design with a population of 360 pregnant women at the Puskesmas Pare District, Kediri Regency. A sample of 190 respondents used purposive sampling technique. The research instrument is a questionnaire. Statistical test using wilcoxon signed rank test. Results: Most of the respondents stated that media advertisements about health protocols were effective, as many as 111 respondents (58.4%). There is an influence of media advertisements on the behavior of implementing health protocols in pregnant women during the pandemic at the Pare Subdistrict Health Center, Kediri Regency in 2022 (p = 0.046). Conclusion: Media advertisements have a good effect on the behavior of implementing health protocols in pregnant women during the pandemic. It is recommended that the use of media advertisements can be increased in quantity as an educational medium for implementing health protocols during a pandemic.